The Effect of Organizational Support and Work Environment on Employee Performance in National Transportation Companies - Dhimas Dwi Nugroho; Akhmad Muzayin; Kartono Kartono (Indonesian Interdisciplinary Journal of Sharia Economics)
This study analyzes the influence of organizational support and work environment on employee performance at National Transportation Companies. Organizational support includes appreciation, assistance, and company concern for employee welfare, while the work environment is reviewed from physical, social, and psychological aspects. This study uses a quantitative approach with an associative design, involving 100 respondents from a total of 1,314 employees who were selected randomly. Data were collected through questionnaires and analyzed using PLS-SEM 3.0. The results show that both organizational support and work environment have a positive and significant effect on employee performance. This finding emphasizes the importance of managing internal factors to improve company performance and services.